PsycEXTRA Dataset 1973
DOI: 10.1037/e465522008-051
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Spatial Density on Social Behavior of Children

Abstract: The behavioral effects of high and low spatial density on normal children of ages 4 and 5 were examined. Sixty Ss were observed in groups of six in a free-play situation under both density conditions. Results showed that there was significantly less aggression and less social interaction in the high-density condition than in the low-dcnsity condition. Thcrc was a significant Density X Sex effect o n aggression and signficant main effects of sex on aggression, nurturance, number of interruptions, and number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0
1

Year Published

1975
1975
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 3 publications
4
48
0
1
Order By: Relevance
“…If the number of people encountered during a recreational experience can detract from an individual's enjoyment of the trip, then the same number of people could also enhance enjoyment for some other individual. Support for this contention has been developed by Wicker (1973) in his study of environmental undermanning and overmanning and is further reinforced by Loo (1973Loo ( , 1974 in a social-spatial model of crowding stress. Heberlein (1977) and Clark and Stankey (1979) agree that density can be too low for some and too high for others in the same recreational setting, but little empirical evidence has been generated to substantiate the point.…”
Section: Related Researchmentioning
confidence: 85%
See 1 more Smart Citation
“…If the number of people encountered during a recreational experience can detract from an individual's enjoyment of the trip, then the same number of people could also enhance enjoyment for some other individual. Support for this contention has been developed by Wicker (1973) in his study of environmental undermanning and overmanning and is further reinforced by Loo (1973Loo ( , 1974 in a social-spatial model of crowding stress. Heberlein (1977) and Clark and Stankey (1979) agree that density can be too low for some and too high for others in the same recreational setting, but little empirical evidence has been generated to substantiate the point.…”
Section: Related Researchmentioning
confidence: 85%
“…More recent studies suggest that perceptions of crowding are related to other variables in addition to the number of visitors encountered, such as expectations and preferences for encounter levels (Heberlein et al, 1979;Schreyer and Roggenbuck, 1978) and previous experience in the area (Vaske et al, 1980;Absher and Lee, 1981). Research conducted in nonrecreation settings also suggests that the feeling of crowdedness is influenced by a variety of types of variables (Altman, 1978;Loo, 1973;Baum et al, 1975).…”
Section: Introductionmentioning
confidence: 92%
“…Adopting a sociological approach, Stokols limits density to a strictly physical meaning: "the number of individuals per unit of space" (Stokols, 1972). With the use of this definition, some authors have suggested that an additional distinction between social and spatial density should also be made (Altman, 1975;Loo, 1973). In a socially dense setting, the high number of individuals in the physical setting is responsible for the dense situation; whereas in the spatially dense situation, the lack of space is responsible for the dense situation.…”
Section: The Complex Nature Of Crowd Issues: Crowding and Density Defmentioning
confidence: 98%
“…Those that were drawn conformed with the findings of more elaborate studies: for example, density was negatively correlated with the amount of social interaction, but did not affect the character of the interactions (cf. Loo, 1972).…”
Section: Projects On Childrenmentioning
confidence: 95%